2018
DOI: 10.1371/journal.pbio.2006532
|View full text |Cite
|
Sign up to set email alerts
|

Call combinations in birds and the evolution of compositional syntax

Abstract: Syntax is the set of rules for combining words into phrases, providing the basis for the generative power of linguistic expressions. In human language, the principle of compositionality governs how words are combined into a larger unit, the meaning of which depends on both the meanings of the words and the way in which they are combined. This linguistic capability, i.e., compositional syntax, has long been considered a trait unique to human language. Here, we review recent studies on call combinations in a pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…Critically, our research provides important initial evidence of the presence of natural call combinations in a vocal learning species (excluding Homo sapiens ), which has interesting implications for theories explaining the evolution of combinatoriality more generally. These results set the foundation for further experimental investigations into syntactic‐like structures in this species—a vital step in furthering our understanding of this largely enigmatic field (Suzuki et al, ; Townsend et al, ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Critically, our research provides important initial evidence of the presence of natural call combinations in a vocal learning species (excluding Homo sapiens ), which has interesting implications for theories explaining the evolution of combinatoriality more generally. These results set the foundation for further experimental investigations into syntactic‐like structures in this species—a vital step in furthering our understanding of this largely enigmatic field (Suzuki et al, ; Townsend et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, alert and recruitment calls in the cooperatively breeding southern pied babbler ( Turdoides bicolor ) are combined into a sequence eliciting mobbing behaviour from conspecifics in the presence of a territorial threat (Engesser et al, ). Experiments demonstrated that the individual calls have independent meanings that are distinct from, but contribute to, the meaning of the mobbing sequence and thus are strongly indicative of rudimentary syntax (Engesser et al, ; see Suzuki et al, , Townsend et al, and Zuidema & de Boer, ). These studies have laid the foundation for further research into basic syntactic abilities in non‐human animals.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, vocalizations involve a far less complex level of organization than human language. Although more and more evidence for syntax is becoming available for some birds and mammals (Coye, Ouattara, Zuberbühler, & Lemasson, ; Ouattara, Lemasson, & Zuberbühler, ), the ability of species to use compositional syntax (or compositionality; see Suzuki, Griesser, & Wheatcroft, ) is still debated (Bolhuis, Beckers, Huybregts, Berwick, & Everaert, ; Petkov & Jarvis, ; Petkov & Wilson, ; Suzuki, Wheatcroft, & Griesser, ). More recently, three studies have examined this issue by studying mobbing calls produced by the Japanese tit, Parus minor , and the southern pied babbler, Turdoides bicolor (Engesser, Ridley, & Townsend, ; Suzuki, Wheatcroft, & Griesser, , ).…”
Section: Introductionmentioning
confidence: 99%
“…When the Japanese tits heard the FME motif combined with the D notes as the compound FME‐D , which is also a natural vocalization, they showed both scanning and approach behaviours. However, there was little or no response when the call order was artificially reversed to D‐FME (i.e., a sequence with unclear or ambiguous meaning; Bolhuis, Beckers, Huybregts, Berwick, & Everaert,; Suzuki et al, ). From this, authors suggest that compositional syntax is a mechanism for information transmission, although some authors have argued that Suzuki and colleagues do not provide any evidence for genuine compositionality in these bird vocalizations (Bolhuis et al, ; Bolhuis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Behaviors are comprised of motor gestures that are sequenced in precise ways, and the manner in which gestures are sequenced can provide information about an individual (e.g., species, individual identity, motivation) [1][2][3][4][5] as well as about environmental context 6,7 . For many important behaviors, including social and communicative behaviors, the structure and sequencing of individual motor gestures can be learned.…”
mentioning
confidence: 99%